Performance Enhancement in Horizontal Axis Wind Turbine Using Blade With Split - Adilkhan Tuken; Cemil Yigit (Wind Energy)
ABSTRACT The positive effects of passive flow control on the blade that uses various methods on the aerodynamic performances of horizontal axis wind turbines (HAWTs) are well‐known. In the current study, splits were made on the blade for passive aerodynamic stall control. A numerical study using computational fluid dynamics (CFD) modeling was conducted to investigate the split impacts on the HAWT blades. The blades are designed using NREL's S819 profile at the root section and NACA 63‐415 profile at the middle and tip sections. Chord length and angle of attack are determined by blade element momentum (BEM) theory. In the optimization process, the slope, position, width, and number of the splits were taken as parameters, and the optimum blade design was created. A steady‐state turbulent flow and transition SST turbulence model was used for the moving reference frame calculation to find the optimum split parameters. The flow in the rotating and stationary zones was solved in an unsteady state by the sliding‐mesh method. Compared with the reference blade, numerical results showed that the power coefficient (Cp) of the single‐split blade with a width of 1.5 mm and a slope of 120° increased to 0.322, an increase of 9.2%. It has been determined that the optimum blade design reaches its maximum Cp at a lower tip–speed ratio (TSR) compared with the reference blade without splits. As a result, the study revealed that using split blades can increase energy production with passive flow control, especially in small‐scale HAWTs.